Enhanced N2 affinity of 1T-MoS2 with a unique pseudo-six-membered ring consisting of N–Li–S–Mo–S–Mo for high ambient ammonia electrosynthesis performance. Issue 2 (23rd December 2020) - Patil, Shivaraj B.; Chou, Hung-Lung; Chen, Yu-Mei; Hsieh, Shang-Hsien; Chen, Chia-Hao; Chang, Chia-Che; Li, Shin-Ren; Lee, Yi-Cheng; Lin, Ying-Sheng; Li, Hsin; Chang, Yuan Jay; Lai, Ying-Huang; et al.
Abstract : Selective electrocatalytic NH3 synthesis using Li intercalated 1T-MoS2 . Abstract : The Haber–Bosch process is widely used to convert atmospheric nitrogen (N2 ) into ammonia (NH3 ). However, the extreme reaction conditions and abundant carbon released by this process make it important to develop a greener NH3 production method. The electrochemical nitrogen reduction reaction (NRR) is an attractive alternative to the Haber–Bosch process. Herein, we demonstrated that molybdenum sulfide on nickel foil (1T-MoS2 –Ni) with low crystallinity was an active NRR electrocatalyst. 1T-MoS2 –Ni achieved a high faradaic efficiency of 27.66% for the NRR at −0.3 V ( vs. RHE) in a LiClO4 electrolyte. In situ X-ray diffraction and ex situ X-ray photoemission analyses showed that lithium ions were intercalated into the 1T-MoS2 layers during the NRR. Moreover, theoretical calculations revealed the differences between six membered rings formed in the 1T-MoS2 and 2H-MoS2 systems with Li intercalation. The bond distances of d (Mo–N) and d (N–Li) of in Li–1T-MoS2 were found to be shorter than those in Li–2H-MoS2, resulting in a lower energy barrier of N2 fixation and higher NRR activity. Therefore, 1T-MoS2 –Ni is promising as a scalable and low-cost NRR electrocatalyst with lower power consumption and carbon emission than the Haber–Bosch process.